2020
DOI: 10.3390/jcm9072268
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibody Production in Asymptomatic and Mild COVID-19 Patients, in Comparison with Pneumonic COVID-19 Patients

Abstract: Objectives: To investigate antibody production in asymptomatic and mild COVID-19 patients. Methods: Sera from asymptomatic to severe COVID-19 patients were collected. Microneutralization (MN), fluorescence immunoassay (FIA), and enzyme-linked immunosorbent assay (ELISA) were performed. Results: A total of 70 laboratory-confirmed COVID-19 patients were evaluated, including 15 asymptomatic/anosmia, 49 mild symptomatic, and 6 pneumonia patients. The production of the neutralizing antibody was observed in 100% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
108
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 35 publications
21
108
2
3
Order By: Relevance
“…suggesting either that they had not been produced or that they had already declined. Accordingly, Ko et al (2020) reported that most asymptomatic and mild COVID-19 patients produced NAbs, although the titers were lower than severe disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…suggesting either that they had not been produced or that they had already declined. Accordingly, Ko et al (2020) reported that most asymptomatic and mild COVID-19 patients produced NAbs, although the titers were lower than severe disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…For screening and confirmation of anti-SARS-CoV-2-binding antibody, we used a two-step protocol that included the FIA IgG kit and two ELISA kits for total and IgG antibody. In a previous study, the FIA IgG kit showed considerable sensitivity (98.8%) even in asymptomatic COVID-19 patients (Ko et al, 2020). The sensitivity of the FIA IgG kit was similar to or higher than that of ELISA kits (98.2% for total antibody and 94.4% for IgG), while ELISA kits were more specific (100% for total antibody and 99.6% for IgG) than the FIA IgG kit (94.1%).…”
Section: Discussionmentioning
confidence: 71%
“…To screen for the production of anti-SARS-CoV-2-binding antibodies among HCWs, we used a fluorescence immunoassay (FIA) kit (AFIAS COVID-19 Ab assay, Boditech Med Inc., Chuncheon, South Korea). In a previous study, FIA immunoglobulin G (IgG) showed considerable sensitivity (98.8%) for a range of conditions, including convalescent sera of asymptomatic patients to severe laboratory-confirmed COVID-19 patients (Ko et al, 2020). In an upcoming study using 110 RT-PCR-positive and 119 control samples, the sensitivity and specificity were 99.1 and 94.1%, respectively (data unpublished).…”
Section: Screening Strategymentioning
confidence: 93%
See 2 more Smart Citations